First trimester placental vascular indices and volume by three-dimensional ultrasound in pre-gravid overweight women. (May 2019) - Chen, C.Y.; Chang, H.T.; Chen, C.P.; Sun, F.J.
Abstract: Objectives: To investigate changes of placental vascular indices and volume in pre-gravid overweight Chinese women during the first trimester using three-dimensional power Doppler ultrasound. Methods: This was a prospective observational study of the morphology of placentas in pre-gravid overweight (body mass index (BMI) ≥ 24 kg/m 2 ) and non-overweight (BMI < 24 kg/m 2 ) Chinese women during the first trimester of pregnancy. Data on placental vascular indices (vascularization index, flow index, and vascularization flow index (VFI)), placental volume, uterine artery pulsatility index (PI), and neonatal outcomes were obtained during the first trimester and analyzed. Linear regression analysis was used to evaluate confounding factors between BMI and ultrasound indices. Results: Of the 429 pregnant women enrolled, 68 (15.9%) were pre-gravid overweight. Placental VFI was significantly lower in the overweight group ( p  = 0.037). Conversely, placental volume was significantly larger in the overweight group ( p  = 0.044), and uterine artery PI was significantly higher in the overweight group ( p  = 0.021). After adjustments for confounding factors, there were still significant differences in placental VFI (unstandardized coefficient (B) −0.666, 95% confidence interval (CI) −1.306 – (−0.025)), placental volume (B 2.458, 95% CI 0.071–4.844), and uterine artery PI (B 0.152, 95% CI 0.030–0.274) between the two groups. Conclusions: Placental vascular indices using three-dimensional power Doppler ultrasound can provide an insight into placental vascularization in pre-gravid overweight women in early pregnancy. Alterations in placental VFI, placental volume, and uterine artery PI occur during the first trimester in pre-gravid overweight women. Highlights: Three-dimensional ultrasound is a practical tool for placental vascular evaluation. Placental vascular indices and volume alter early in overweight women. Maternal obesity could result in early changes of placental endothelial structure.